'Can I tell?' Children's participation and positioning in a secretive atmosphere in family therapy. Issue 1 (4th May 2020) - Helimäki, Mira; Laitila, Aarno; Kumpulainen, Kirsti
Abstract : As a multifaceted phenomenon, family secrets affect interaction in the therapeutic system. This qualitative study, applying the multi‐actor Dialogical Methods for Investigations of Happening of Change, explored how children participated and positioned themselves in family therapy in a climate of family secrets. The results showed that the children were active co‐participants in the complex dynamics of a secretive atmosphere, involving themselves in the paradoxical processes of reconstructing and deconstructing the secretive and unsafe climate. In family therapy, a child's symptomatic behaviour can function as a visible 'cover story' for invisible constructions of secrets, preventing sensitive topics from becoming the focus of therapy. Family secrets therefore continue to present a challenge in family therapy practice and research. Practitioner points: Family secrets should be asked about in pre‐therapy assessment and diagnostic interviews where all family members are present The genogram enables the exploration of multigenerational family patterns and functions that might be influenced by family secrets By normalising the phenomenon of family secrets, therapists could make room for joint discussions on these and encourage family members to talk about their good reasons for keeping secrets 抽象: "我能说吗？"秘密氛围下的家庭治疗中儿童的参与和定位 作为一种多层面的现象，家庭秘密影响着治疗系统中的互动。这项定性研究运用多角色的"研究变化发生的对话方法"来探讨在家庭秘密的氛围下，儿童如何参与家庭治疗以及在其中的定位。结果显示，儿童在秘密氛围的复杂动态中是积极的参与者，同时涉及到重建和解构秘密、不安全氛围的矛盾过程。在家庭治疗中，孩子的症状性行为可以作为隐藏秘密的表面"借口"，防止敏感话题成为治疗的焦点。因此，家庭秘密在家庭治疗实践和研究中仍然是一个挑战。 对从业者的启示: 在所有家庭成员都在场的治疗前评估和诊断性访谈中，应询问家庭秘密 家系图能够探索可能受家庭秘密影响的多代家庭模式和功能 通过使家庭秘密的现象正常化，治疗师可以创造空间共同讨论这些问题，并鼓励家庭成员谈论他们保守秘密的正当理由 Resumen: "¿Puedo decirlo?" La participación y el posicionamiento de los niños en un ambiente de secretismo en la terapia familiar Como fenómeno multifacético, los secretos familiares afectan la interacción en el sistema terapéutico. Este estudio cualitativo, aplicando el Método Dialógico para Investigación de la Ocurrencia de Cambio con multiples participantes, exploró cómo los niños participaron y se posicionaron en la terapia familiar en un clima de secretos familiares. Los resultados mostraron que los niños eran co‐participantes activos en la dinámica compleja de una atmósfera de secretismo, involucrándose ellos mismo en los procesos paradójicos de reconstrucción y deconstrucción de un ambiente secreto e inseguro. En la terapia familiar, el comportamiento sintomático de un niño puede funcionar como una "historia de portada" visible para construcciones invisibles de secretos, evitando que temas sensibles se conviertan en el foco de la terapia. Los secretos familiares, por lo tanto, continúan presentando un desafío en la práctica de la terapia familiar y la investigación. Puntos de implicación práctica: Se debe preguntar sobre los secretos familiares en la evaluación previa a la terapia y en las entrevistas de diagnóstico donde todos los miembros de la familia están presentes El genograma permite la exploración de patrones y funciones familiares multigeneracionales que pueden estar influenciados por los secretos familiares. Al normalizar el fenómeno de los secretos familiares, los terapeutas podrían hacer espacio para discusiones conjuntas sobre estos y alentar a los miembros de la familia a hablar sobre sus buenas razones para guardar secretos.